Managerial Capital and the Market for CEOs - Kevin J. Murphy; Jan Zabojnik (Queen's University, Department of Economics, 2006)
This paper reconciles two pronounced trends in U.S. corporate governance: the increase in pay levels for top executives, and the increasing prevalence of appointing CEOs through external hiring rather than internal promotions. We propose that these trends reflect a shift in the relative importance of "managerial ability" (transferable across companies) and "firm-specific human capital" (valuable only within the organization). We show that if the supply of workers in the corporate sector is relatively elastic, an increase in the relative importance of managerial ability leads to fewer promotions, more external hires, and an increase in equilibrium average wages for CEOs. We test our model using CEO pay and turnover data from 1970 to 2000. We show that CEO compensation is higher for CEOs hired from outside their firm, and for CEOs in industries where outside hiring is prevalent.
Keywords: J24; J31; J63; 330; CEO pay; CEO turnover; General skills; Firms specific skills; Corporate Governance; Führungskräfte; Führungskräfteauswahl; Lohn; Qualifikation; USA